2009
DOI: 10.1158/0008-5472.can-08-3231
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Off-Resonance Saturation Magnetic Resonance Imaging of αvβ3-Targeted Superparamagnetic Nanoparticles

Abstract: Magnetic resonance imaging is a powerful clinical imaging technique that allows for noninvasive tomographic visualization of anatomic structures with high spatial resolution and soft tissue contrast. However, its application in molecular imaging of cancer has been limited by the lack of sensitivity and detection accuracy in depicting the biochemical expression of these diseases. Here, we combine an ultrasensitive design of superparamagnetic polymeric micelles (SPPM) and an off-resonance saturation (ORS) method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 24 publications
0
83
0
Order By: Relevance
“…The neovasculature of the tumors was clearly manifested by a 4.7 T animal MRI scanner, and the imaging efficacy was further enhanced by an off-resonance saturation technique. 62 Tumor accumulation of cRGD-encoded SPPM was corroborated by a biodistribution study, which indicated that tumor uptake of cRGD-encoded SPPM (1.3% ± 0.3% ID/g) was significantly higher than that of cRGD-free SPPM (0.6% ± 0.3% ID/g). However, most of the micelles were sequestered by spleen (∼10% ID/g) and liver (∼4% ID/g).…”
Section: Imaging With Spion Clustersmentioning
confidence: 78%
“…The neovasculature of the tumors was clearly manifested by a 4.7 T animal MRI scanner, and the imaging efficacy was further enhanced by an off-resonance saturation technique. 62 Tumor accumulation of cRGD-encoded SPPM was corroborated by a biodistribution study, which indicated that tumor uptake of cRGD-encoded SPPM (1.3% ± 0.3% ID/g) was significantly higher than that of cRGD-free SPPM (0.6% ± 0.3% ID/g). However, most of the micelles were sequestered by spleen (∼10% ID/g) and liver (∼4% ID/g).…”
Section: Imaging With Spion Clustersmentioning
confidence: 78%
“…Further, PEG-g-PEI is synthesized by introducing PEG to polyethylenimine to reduce cytotoxicity and suppress nonspecific interactions of polyethylenimine with blood components. 30,31 Moreover, PEG-g-PEI could complex 13,14,32 In this study, PEG-g-PEI-SPION and scFv CD44v6 were chosen as two essential components to construct a targeted siRNA delivery vector with MRI imaging functions. ScFv CD44v6 was generated by phage display technology as described in our previous study, and its cancer-targeting ability in vitro has been demonstrated by immunofluorescent staining, Western blotting, and flow cytometric analyses.…”
Section: Discussionmentioning
confidence: 99%
“…MRI-visible nanoparticulate systems have been used for anticancer drug delivery and molecular imaging of cancer. 13,14 To construct a nanoparticulate carrier combining siRNA delivery and MRI function, superparamagnetic iron oxide nanoparticles (SPION), known to be a highly efficient T 2 contrast agent for MRI, was attached to PEG-g-PEI (PEGg-PEI-SPION), making the vector MRI-visible. 15 Antibodies have great potential to be applied as targeting ligands for antibody-mediated diagnostic and therapeutic agents because of their high specificity and affinity for target antigens.…”
Section: Introductionmentioning
confidence: 99%
“…This method relies on diffusion-mediated saturation transfer to reduce the on-resonance MRI signal due to the off-resonance saturation (ORS) pulse, similar to chemical exchange saturation transfer techniques (Ward, 2000). This approach has been verified that greatly improved tumor detection accuracy over the conventional T 2 *-weighted methods because of its ability to turn "ON" the contrast of superparamagnetic polymeric micelles (SPPM) nanoparticles (Khemtong, 2009). SPPM nanoparticles encoded with cyclic (RGDfK) ligand (arginine-glycine-aspartic acid), cRGD, were able to target the v 3 -expressing microvasculature in A549 non-small cell lung tumor xenografts in mice.…”
Section: Off-resonance Imaging (Ori)mentioning
confidence: 99%
“…The same micelles were previously conjugated with a cRGD ligand that can target v 3 integrins on tumor endothelial (SLK) cells (Nasongkla, 2006), illustrating growth inhibition of tumor SLK cells with ultrasensitive detection by MRI. The same lab in University of Texas Southwestern Medical Center at Dallas has previously demonstrated a multi-functional micelle design that allows for the vascular targeting of tumor endothelial cells, MRI ultrasensitivity, and controlled release of doxorubicin (Doxo) for therapeutic drug delivery (Nasongkla, 2006;Khemtong, 2009). Investigators (Guthi, 2010) found that SPIO-clustered polymeric micelle design has considerably decreased the MR detection limit to subnanomolar concentrations (< nM) of micelles through the increased T 2 relaxivity and high loading of SPIO per micelle particle; suggested that, on that multifunctional platform, the application of positive contrast imaging, such as ORS, could further enhance the contrast sensitivity and allow for the in vivo imaging of tumor-specific markers.…”
Section: Imaging Contrast Of Iron-labeled Cell On Multimodular Platformmentioning
confidence: 99%